2006
DOI: 10.1073/pnas.0510284103
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor variant III mutations in lung tumorigenesis and sensitivity to tyrosine kinase inhibitors

Abstract: The tyrosine kinase inhibitors gefitinib (Iressa) and erlotinib (Tarceva) have shown anti-tumor activity in the treatment of non-small cell lung cancer (NSCLC). Dramatic and durable responses have occurred in NSCLC tumors with mutations in the tyrosine kinase domain of the epidermal growth factor receptor (EGFR). In contrast, these inhibitors have shown limited efficacy in glioblastoma, where a distinct EGFR mutation, the variant III (vIII) in-frame deletion of exons 2-7, is commonly found. In this study, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
175
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 37 publications
7
175
0
3
Order By: Relevance
“…The information concerning whether EGFRvIII mutation is associated with specific histological types of lung cancer is conflicting, although most studies have indicated that EGFRvIII is associated with squamous cell carcinoma. 98,99 In the study by Sasaki et al, 97 EGFRvIII mutation was detected in 3% (8/ 252) of non-selected lung cancer patients. All patients bearing a EGFRvIII mutation were male, smokers, and seven had squamous cell carcinoma, whereas one had poorly differentiated adenocarcinoma.…”
Section: Egfrviii Mutationmentioning
confidence: 98%
See 1 more Smart Citation
“…The information concerning whether EGFRvIII mutation is associated with specific histological types of lung cancer is conflicting, although most studies have indicated that EGFRvIII is associated with squamous cell carcinoma. 98,99 In the study by Sasaki et al, 97 EGFRvIII mutation was detected in 3% (8/ 252) of non-selected lung cancer patients. All patients bearing a EGFRvIII mutation were male, smokers, and seven had squamous cell carcinoma, whereas one had poorly differentiated adenocarcinoma.…”
Section: Egfrviii Mutationmentioning
confidence: 98%
“…EGFRvIII mutations were found in 5% of human lung squamous cell carcinomas (also see prior discussion) (Figure 4). 98,99 The advent of targeted therapy based on driver mutations in lung adenocarcinoma has countered the notion that non-small cell lung cancer (NSCLC) is a distinct clinical entity. Current information indicates that distinguishing a tumor as NSCLC alone is no longer sufficient for patient management and the term 'non-small cell lung cancer (NSCLC)' should be abandoned.…”
Section: Other Alterations That Affect the Egfr Tki Responsementioning
confidence: 99%
“…Decreased response to therapy with cisplatin and cetuximab was reported in head and neck SQCCs (HNSCCs) harboring this variant [104]. Evidence from a cell line study also suggests that EGFR vIII harboring tumors are relatively resistant (Ͼ40 fold more resistant compared with L858R variant) to gefitinib and erlotinib [102]. Although strategies capable of targeting this variant have been described in the literature, none are currently available for clinical use [105].…”
Section: Egfrmentioning
confidence: 99%
“…We performed RT -PCR separately for EGFRvIII and the housekeeping gene GAPDH. Primers were 5 0 -GGGCTCTGGAGGAAAAGAAA-3 0 and 5 0 -AGGCC CTTCGCACTTCTTAC-3 0 for amplifying EGFRvIII and wtEGFR (Ji et al, 2006), and 5 0 -CACCCACTCCTCCACCTTTG-3 0 and 5 0 -CCAC CACCCTGTTGCTGTAG-3 0 for amplifying GAPDH. The protocol was as follows: initial denaturation at 951C for 10 min, followed by 30 (EGFRvIII) or 25 cycles (GAPDH) of amplification (1 min at 951C, 1 min at 561C for EGFRvIII and at 601C for GAPDH, and 90 s at 721C) and a final extension step at 721C for 7 min.…”
Section: Rt -Pcr For Egfrviiimentioning
confidence: 99%